Solvation enthalpy and the thermodynamics of hydration of trans-cyclohexyl-1,4-diamine and cis-cyclohexyl-1,2-diamine - Tomé, Luciana I. N. (2007)
The enthalpy of solution of trans-cyclohexyl-1,4-diamine and cis-cyclohexyl-1,2-diamine in water was determined by calorimetry. The enthalpy of hydration was determined from this quantity and from the enthalpy of sublimation/vaporization presented in another paper by the authors. Considering the solvation process resulting from cavity creation in the solvent and variation of solute conformation transfer steps, the enthalpy corresponding to solute-solvent interaction was estimated. The entropies of solvation and interaction were calculated from the values given for the enthalpies in the present paper and those available for the Gibbs free energies.